2017
DOI: 10.1016/j.bbr.2017.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases mTOR signaling in brain regions involved in cognition and emotional behavior

Abstract: Exercise can enhance learning and memory and produce resistance against stress-related psychiatric disorders such as depression and anxiety. In rats, these beneficial effects of exercise occur regardless of exercise controllability: both voluntary and forced wheel running produce stress-protective effects. The mechanisms underlying these beneficial effects of exercise remain unknown. The mammalian target of rapamycin (mTOR) is a translation regulator important for cell growth, proliferation, and survival. mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 120 publications
1
46
0
4
Order By: Relevance
“…Despite the unclear status of ERK activation in the cortex, these studies suggest that mGluR1/5 signaling pathways are functioning differently in the cortex and the hippocampus. In line with this notion, a recent study of mTOR activity and exercise demonstrated that the activation status of mTOR is depending on the brain region, the cell type (neuron or glia) and the type of exercise (sedentary, voluntary or forced; Lloyd et al, 2017 ).…”
Section: The Fragile X Syndrome — Of Micementioning
confidence: 88%
“…Despite the unclear status of ERK activation in the cortex, these studies suggest that mGluR1/5 signaling pathways are functioning differently in the cortex and the hippocampus. In line with this notion, a recent study of mTOR activity and exercise demonstrated that the activation status of mTOR is depending on the brain region, the cell type (neuron or glia) and the type of exercise (sedentary, voluntary or forced; Lloyd et al, 2017 ).…”
Section: The Fragile X Syndrome — Of Micementioning
confidence: 88%
“…The prefrontal cortex (mPFC), particularly the infralimbic region, is well known to be involved in fear extinction learning and memory (Do-Monte et al 2015;Giustino and Maren 2015), and it is possible that exercise facilitates prefrontal mechanisms underlying extinction. Plasticity factors such as BDNF (Neeper et al 1995) and mammalian target of rapamycin (Lloyd et al 2017) are increased in the mPFC following at least a few days of wheel running, although whether a few hours of wheel running is enough to up-regulate plasticity factors in the mPFC is unknown. If exercise enhances fear extinction through mPFC mechanisms, one might expect that the infralimbic region of the mPFC would be more active during recall of fear extinction in exercising rats, as the infralimbic region is involved in fear extinction recall (Thompson et al 2010;Chang and Maren 2011) and has been reported to express high levels of immediate early genes in rats with strong fear extinction memory (Knapska and Maren 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine, as a tyrosine precursor, is a substrate for tyrosine hydroxylase in the rate-limiting step in catecholamine synthesis [40]. Threonine regulates mTOR signaling [41], which is stimulated in the hippocampus and other brain structures of exercised rodents [42]. Galactose-6-phosphate is in constant equilibrium with fructose-6-phosphate, and the positive correlation between these two compounds was significant in the hippocampi of the running mice (r = 0.82, p < 0.05; data not shown).…”
Section: Cortical and Hippocampal Metabolites Correlate With Activitymentioning
confidence: 99%